Instant global illumination on the GPU using OptiX - Marques, Ricardo (2010)
OptiX, a programmable ray tracing engine, has been recently made available by NVidia, relieving rendering researchers from the idiosyncrasies of efficient ray tracing programming and allowing them to concentrate on higher level algorithms, such as interactive global illumination. This paper evaluates the performance of the Instant Global Illumination algorithm on OptiX as well as the impact of three di fferent optimization techniques: imperfect visibility, downsampling and interleaved sampling. Results show that interactive frame rates are indeed achievable, although the combination of all optimization techniques leads to the appearance of artifacts that compromise image quality. Suggestions are presented on possible ways to overcome these limitations.